Comparative Review for the Edges among JS Frameworks: Angular vs React in Web Application Development - Batoon, Jayson A.; Calizon, John Michael (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
JavaScript frameworks have revolutionized modern web development by providing structured solutions for building dynamic and interactive applications. However, challenges arise when these frameworks encounter edge cases — scenarios that fall outside typical usage patterns. This study investigates the handling of edge cases across popular JavaScript frameworks, utilizing the IMRAD (Introduction, Method, Results, and Discussion) format to present findings systematically. Through a combination of literature review, practical experimentation, and code analysis, the research examines how different frameworks address uncommon yet critical scenarios that could impact application performance and user experience. This is supported by metrics from the 2023 Stack Overflow Developer Survey, GitHub activity trends, and js-framework-benchmark results, offering quantifiable comparisons across performance, popularity, and development efficiency. Results reveal varying levels of robustness, with certain frameworks demonstrating advanced mechanisms to mitigate edge cases effectively. Conversely, others require significant manual intervention to ensure stability. These findings offer valuable insights for developers and decision-makers in selecting the most appropriate framework for complex, real-world projects. The study concludes with recommendations for enhancing edge case management within JavaScript frameworks, aiming to improve the reliability and resilience of web applications.